2018
DOI: 10.4274/balkanmedj.2016.1110
|View full text |Cite
|
Sign up to set email alerts
|

GDF9 and BMP15 Expressions and Fine Structure Changes During Folliculogenesis in Polycystic Ovary Syndrome

Abstract: Background:Polycystic ovary syndrome is the most frequently seen endocrine disorder in women of reproductive age with a prevalence of about 10%.Aims:To investigate the efficiency of growth differentiation factor 9 and bone morphogenetic protein 15 during folliculogenesis in a dehydroepiandrosterone-induced mouse Polycystic ovary syndrome model.Study Design:Animal experimentation.Methods:Mice were divided into 3 groups: control, vehicle and Polycystic ovary syndrome. Polycystic ovary syndrome model mice were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…In this study, the expression level of GDF9 was lower in preantral PCOS follicles. Karagul et al [ 6 ] also found reduced levels of GDF9 expression in primary follicles. Teixeira Filho et al [ 52 ] also reported the aberrant expression of GDF9 in oocytes of women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the expression level of GDF9 was lower in preantral PCOS follicles. Karagul et al [ 6 ] also found reduced levels of GDF9 expression in primary follicles. Teixeira Filho et al [ 52 ] also reported the aberrant expression of GDF9 in oocytes of women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Folliculogenesis is fundamentally based on the secretion of various types of growth factors (GFs) by ovarian somatic cells [ 5 ]. Two major types of GFs are growth differentiation factor-9 (GDF9) and transforming growth factor-beta1 (TGF-β1) [ 6 , 7 ], which are necessary for folliculogenesis and cell proliferation, respectively. Bone morphogenetic protein (BMP)-15 is involved in folliculogenesis, including the growth and maturation of ovarian follicles, regulation of the sensitivity of granulosa cells to follicle-stimulating hormone (FSH), determination of the number of ovulated follicles, and prevention of granulosa cells from apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the BMP15 and GDF9 play a critical role in follicle development, oocyte maturation, ovulation, and embryo development [61]. However, the in vivo and in vitro studies have suggested that GDF9 and BMP15 polymorphism contribute to the formation of the pathogenesis of PCOS [3,62]. The A-G transition at position 704 of the BMP15 gene results in a nonconserved substitution of Y235C in the pro region of BMP15 proprotein that was associated with hypergonadotropic ovarian failure in women [4].…”
Section: Discussionmentioning
confidence: 99%
“…The follicles of patients with PCOS have polycystic ovaries with an increase in matrix hypertrophy; the granular cell substrate is thickened, and the electron density in the zona pellucida formed by secondary follicles increases. Ovarian drilling is often used for clinical treatment, and the mechanical forces generated in the process cause changes in the ovarian endocrine level, especially an luteinizing hormone decline (97,98). Presently, a mechanobiology-based treatment that ruptures the ovarian cortex through in vitro activation (IVA) temporarily interrupts the Hippo pathway and promotes the secondary development of follicles.…”
Section: Benign Ovarian Diseases and Biomechanics Polycystic Ovary Syndromementioning
confidence: 99%